The Dark Tetrad at Work. Issue 5 (19th October 2020) - Thibault, Tabatha; Kelloway, E. Kevin
ABSTRACT: The purpose of this study was to create and validate a short workplace-specific measure of the Dark Tetrad (i.e., narcissism, Machiavellianism, psychopathy, and sadism) that could be used by researchers, practitioners, and organizations. In Study 1, a two-wave longitudinal design (T1: N = 416; T2: N = 209) was used to develop and evaluate a 22-item scale that assessed the four dimensions. Each scale trait was positively associated with, and predicted, workplace deviance. The factor structure of the scale was replicated in a second sample ( N = 289). These results have implications for developing new research on the Dark Tetrad in the workplace.